2015
DOI: 10.1007/8904_2015_479
|View full text |Cite
|
Sign up to set email alerts
|

Periventricular Calcification, Abnormal Pterins and Dry Thickened Skin: Expanding the Clinical Spectrum of RMND1?

Abstract: Background: We report a consanguineous Sudanese family whose two affected sons presented with a lethal disorder characterised by severe neonatal lactic acidosis, hypertonia, microcephaly and intractable seizures. One child had additional unique features of periventricular calcification, abnormal pterins and dry thickened skin.Methods: Exome enrichment was performed on pooled genomic libraries from the two affected children and sequenced on an Illumina HiSeq2000. After quality control and variant identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Fourteen patients from 11 families (P1–P9, P10.1, P10.2, P11.1) are new cases; their clinical details are provided in online supplementary data 1. Authors from the previously published cases5 6 8 (P11.2, P12–P18.2) also completed the case report form and provided additional data for this study (P11.2, P12–P16, online supplementary data 1). Clinical data were extracted from the literature for the remaining eight patients (P19 to P21.5) 2–4…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen patients from 11 families (P1–P9, P10.1, P10.2, P11.1) are new cases; their clinical details are provided in online supplementary data 1. Authors from the previously published cases5 6 8 (P11.2, P12–P18.2) also completed the case report form and provided additional data for this study (P11.2, P12–P16, online supplementary data 1). Clinical data were extracted from the literature for the remaining eight patients (P19 to P21.5) 2–4…”
Section: Resultsmentioning
confidence: 99%
“…The clinical phenotypes associated with RMND1 mutations are expanding, ranging from a fatal, infantile encephalomyopathy with lactic acidosis2 5 to a less severe phenotype characterised by developmental delay, congenital sensorineural deafness, hypotonia and renal disease 46 In this study, we identified new patients harbouring recessive mutations in RMND1 from several metabolic clinics and research centres across Europe (UK, Ireland, Italy, Denmark, Spain and Czech Republic) and the USA.…”
Section: Introductionmentioning
confidence: 99%
“…RMND1 gene mutations have been linked to mitochondrial disease with varying severity and variable multisystem involvement [ 2 , 9 13 ]. However, all cases presented with deafness and some element of neuromuscular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have successfully described a molecular basis of the disease diversified phenotypic spectrum using whole exome sequencing (WES) (Taylor et al, 2014; Ng et al, 2016; Casey et al, 2016). WES analysis facilitates rapid molecular diagnosis of clinically challenging cases and their family members by providing a quick and comprehensive information about known or novel mutations in candidate genes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that various novel and common recessive mutations in RMND1 are associated with multiple phenotypes characterized by delayed maturation of vision, developmental delay, dilated cardiomyopathy, deafness and neurological defects (Gupta et al, 2016), renal tubular acidosis type 4 presented as hyponatraemia and hyperkalaemia and cystic/hypoplastic kidneys (Ng et al, 2016). Likewise, complex clinical spectrum of patients with RMND1 mutations is emerging with infantile encephalomyopathy with lactic acidosis (Garcia-Diaz et al, 2012, Casey et al, 2016) to a less severe form of developmental delay, hypotonia, renal disease and congenital sensorineural deafness (Janer et al, 2015). Therefore, molecular screening of RMND1 gene will help identify the inheritance mode of causative genetic mutations in patients with renal and or neurological defects.…”
Section: Introductionmentioning
confidence: 99%